Bainite Structures in 0.2C-3.6M Steel - Joarder A.; Sarma D.S. (My University, 2025)
The microstructures of a 0.2C-3.6Ni steel are studied after isothermal transformation over a temperature range of 600–400°C after different times up to 10 ks at each temperature. It was observed that the transformation at 600°C and 500°C for short durations has led to the formation of Widmanstätten ferrite-martensite structures (the later formed as a result of transformation during cooling of untransformed austenite) which on further holding led to the formation of cementite allotriomorphs at ferrite grain boundaries (at 600°C) or bainite (at 500°C) structures. This reveals that the ferrite-martensite structures, referred to as BI type of bainite proposed by earlier investigators is not bainitic in nature. Transformation at 450°C resulted in mixed structures of upper bainite and lath-type lower bainite while lath type lower bainite only formed at 400°C. It was found that nickel has strong stabilising effect on retaining austenite films at the lath boundaries of martensite as compared with manganese or molybdenum. © 1991, The Japan Institute of Metals. All rights reserved.